Business Plan: Community Business Incubator for Scaling Independent Designers in Qatar - Bachir, Abir (2012)
Local design is a business incubator that seeks to scale design and designers in Qatar within the category of furnishings, home wear and apparel. Meeting larger social objectives includes increasing national entrepreneurial activity and decreasing the gender gap through the provision of accessible opportunities in design. Our products reflect individual and regional pride. Our processes utilize efficient operational resources while infusing social responsibility in a growing economy. The World Economic Forum identified the community business incubator model as economic tool for seeding entrepreneurs and scaling brands sustainably in developing countries by ensuring fast yet stable growth. The model reduces non-systematic risk, allowing entrepreneurs to focus their efforts and resources on scaling their brand. Local design seeks to establish 150 relationships with aspiring local designers, repurposing through novel design, home wear and apparel. The aim is to launch 100 incubator brands in year 1. From year 2 onwards, we aim to add 50 independent design entrepreneurs to our portfolio annually. By providing consulting services, speed mentorship and networking opportunities we aim to scale brands in Qatar and identify strong local lines for regional distribution. Showcasing of the incubator’s brands is en-suite. We take a 15 – 30% commission on items and charge for extended premier services. The business model provides incubator incumbents with real-time access to the market. This environment allows aspiring designers to hone their managerial and entrepreneurial skills by calibrating their brand against aggregated demand. This learning process is facilitated by a main feature of our operations, our uniquely designed ERP and networking software.